THE DYNAMICS OF ISLAMIC COUNSELING IN THE STATE ISLAMIC SENIOR HIGH SCHOOL (MAN) AT MEDAN CITY, NORTH SUMATRA - Abdurrahman Abdurrahman Abdurrahman; Saiful Akhyar Lubis; Lahmuddin Lubis Lubis (State Islamic University of North Sumatra Indonesia, 2018)
This study aims to determine the dynamics of Islamic counseling practices throughout State Islamic Senior High School (MAN) in the city of Medan. This study, using a qualitative approach, which attempts to explore the phenomena that occur in the four research sites in question, then reduced and describe using descriptive explanation. This research was conducted in the State Islamic Senior High School (MAN) all over Medan City (MAN 1, MAN 2 Model, MAN 3, MAPN 4 Medan). The findings obtained that the practice of implementing Islamic counseling uses several services, including: Orientation services, Information services, placement and distribution services, content mastery services, group counseling services, individual counseling services, mediation services, consulting services, referrals, data sets and others. Those are elaborated with the values of Islamic teachings, both attitudes and materials (counselor attitudes / BK teachers who do not distinguish the background of counselees / students violate or not violate, Islamic content material, and soft speech). So it can attract counselees / students to explore the problems encountered and the settlement step of triadic communication (God, Counselor, Counselee / student)